Phase Behavior of Pseudo-Ternary Gemini Surfactant + 1-Hexanol/Oil/Water Systems. (14th November 2012) - Rozaini, Mohd Zul Helmi
Abstract : Temperature dependent phase behavior of pseudo-ternary Gemini surfactant + 1-hexanol (1 : 5 molar ratios)/oil/water systems is reported from 0°C to 65°C. The influence of nature of hydrocarbon oil and type of electrolytes (weak as well as strong) has been investigated on the temperature induced phase behavior of the ternary system. At surfactant concentration, Φ s = 40 %, a "nose-shaped" microemulsion region is observed. Below one-phase microemulsion region, L α phase appears. The presence of NaCl decreases the domain size of 1 Φ micellar region whereas oxalic acid first decreases the domain below Φ w < 18 and then increases above Φ w > 18 in the lower boundary of the phase diagram. The critical weight fraction of water Φ w cri decreases in presence of both electrolytes. However, Φ w max increases in presence of oxalic acid and remains constant in presence of NaCl as compared to salt-free system. Furthermore, when cyclohexane was replaced by a longer straight chain hydrocarbon, dodecane, the domain of the one-phase microemulsion region is tremendously increased.